The disruption of the feminine in Henry James - Walton, Priscilla L. (Heritage., 1992)
The women of Henry James's novels have intrigued critics for a hundred years. Priscilla Walton brings a post-structuralist feminist perspective to James's work. Drawing on the theories of Jacques Derrida, Helene Cixous, Julia Kristeva, and Luce Irigaray, she focuses on the constructed Otherness of the Feminine. Traditional critics of James have tried to unify and hence confine his works, but in so doing they have ignored the polyvalent nature of his writings. Walton challenges such limited readings by opening up the texts to interpretation and tracing the ways in which the narratives resist closure. She contends that in James's texts the representations of women foreground the limitations that Realist Masculine referentiality has placed on both the Feminine text and the female characters. Because women have no singular presence within Masculine ideology, they cannot be fixed and it is their Otherness which generates the plurality that is privileged in the late works. Walton examines The Turn of the Screw, Roderick Hudson, The Portrait of a Lady, a selection of short stories, and the three novels of the Major Phase. She traces a development within these writings, and argues that, where the early works comprise efforts to confine and grasp the Feminine Other, the later texts implicitly recognize and delight in its fecundity. The texts themselves demonstrate that it is the Feminine Other which gives birth to artistic creation.